Development of a Mobile Learning-Based Education and Training System to Improve Professional Competence of Vocational High School Teachers - Maheswari, Zahra Akira; Kusumawardani, Rini; Hudallah, Noor (Universitas Negeri Semarang, 2024)
This study was conducted to address the gap between the professional competence of vocational high school teachers and the competency standards established by the Regulation of the Minister of National Education Number 16 of 2007 and the Decree of the Directorate General of Teachers and Education Personnel Number 2626/B/HK.04.01/2023 regarding the Teacher Competency Model. Limited access to conventional education and training also contributes to this issue. The objective of this research is to develop a mobile learning-based training system using multi-platform integration that is engaging, effective, and adaptive in order to enhance the professional competence of vocational high school teachers.The development process applied the ADDIE model through five comprehensive stages. In the analysis stage, a needs assessment survey identified an urgent need for technology-based training. During the design stage, various components of the mobile learning system were structured. The development stage involved expert validation, and the system was rated as “Highly Feasible” by media experts. In the implementation stage, the system was delivered online and involved 230 vocational high school teachers. The evaluation stage showed an increase in the average score from 15.62 in the pre-test to 18.84 in the post-test, with an N-Gain score of 0.74, categorized as high. Additionally, participants rated the system as “Very Engaging”, with an attractiveness score of 3.6 out of 4, equivalent to 90%.The findings indicate that the mobile learning-based education and training system developed in this study is effective in improving the professional competence of vocational high school teachers.